EFFECT OF PRE- ANC POSTCALVING SUPPLEMENTATION OF PRIMIPAROUS NELLORE DONOR COWS WITH SOURCES OF POLYUNSATURATED FATTY ACIDS ON THE NUMBER OF OOCYTES OBTAINED IN VIVO AND IN VITRO EMBRYO PRODUCTION - Rossi, Guilherme Fazan [UNESP]; Monteiro, Fabio Morato; De Lima, Marina Ragagnin [UNESP]; Vantini, Roberta [UNESP]; Ribeiro, Enilson Geraldo; Zerlotti Mercadante, Maria Eugenia; Garcia, Joaquim Mansano [UNESP] (Inst Zootecnia, 2015)
The objective of this study was to evaluate the effects of feeding primiparous Nellore cows supplements rich in protected or unprotected linoleic (n-6) and linolenic (n-3) acids before and after calving on the number of follicles, total number of cumulus-oocyte complexes (COCs) collected by aspiration (OPU) and oocytes suitable for culture (grades I, II and III), and in vitro embryo production (IVEP). The donor cows were randomly divided into three groups: control (n=7), Megalac-E (R) (n=8; 100 g/donor/day), and flaxseed (n=7; 1.0 kg/donor/day). The diets were offered at least 30 days precalving and 75 days postcalving. The animals were submitted to OPU on postcalving days 30, 45, 60 and 75. Recovered oocytes were selected and those considered suitable for culture were submitted to the IVEP procedures. The data were analyzed using a completely randomized design with repeated measures over time. There was no effect of supplementation on the number of follicles, the number of recovered COCs and those suitable for culture, or IVEP. However, the rate of oocytes suitable for culture recovered by OPU was higher on postcalving days 60 and 75 when compared to days 30 and 45. Additionally, the rate of embryos produced in vitro increased after postcalving day 45. In conclusion, pre- and postcalving supplementation with 100 g/day Megalac-E (R) or 1.0 kg/day flaxseed does not alter the number of oocytes obtained in vivo or IVEP rates of lactating primiparous Nellore donor cows. However, IVEP improves when the programs are carried out 45 days after calving.
Keywords: IVEP; Nellore; oocytes; polyunsaturated fatty acids; ostcalving